Association Between Adolescent Pregnancy and Stunting Incidence: A Scoping Review - Nafisah, Khilda Durrotun; Astuti, Andari Wuri (Jurnal Promosi Kesehatan Indonesia, 2024)
Background: Stunting is a developmental disorder that occurs in children caused by malnutrition, frequent infections, and poor psychosocial simulation. Stunting can be influenced by some factors such as infection, exclusive breastfeeding, early initiation of breastfeeding, and adolescent pregnancy. This study aims to review the association between adolescent pregnancy and stunting incidence.Method:  This scoping review used the PRISMA-ScR framework by searching for articles from relevant databases such as Pubmed, EBSCO, and Wiley. The article search obtained ten articles for further analysis. The article was analyzed based on the Joanna Briggs Institute (JBI). The keywords used were Teen Pregnancy* OR Adolescent Pregnancy* OR Teen Pregnancies* AND Nutritional Deficiency* OR Undernutrition* OR Growth Disorder* OR Stunting*. Besides, the researcher added a filter, namely articles published in the last five years (2018-2022), articles that are open access, and original research articles.Results: Based on the results of reviewing the ten articles, it can be concluded that adolescent pregnancy is significantly associated with stunting incidence in adolescents with low education levels and poor economic conditions leading to poor health awareness and nutritional status. Future studies are expected to further evaluate the relationship between adolescent pregnancy and stunting incidence